2012
DOI: 10.1007/s10008-012-1938-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrolytic generation of oxygen gas at binary nickel oxide–cobalt oxide nanoparticle-modified electrodes

Abstract: This study addresses the enhancement of the oxygen evolution reaction (OER) on glassy carbon, Au, and Pt electrodes modified with binary catalysts composed of nickel oxide nanoparticles (nano-NiO x ) and cobalt oxide nanoparticles (nano-CoO x ). Binary NiO x /CoO x -modified electrodes (with NiO x initially deposited) show a high catalytic activity and a marked stability which far exceeds that obtained at the individual oxide-modified electrodes. This enhancement is demonstrated by a marked negative shift (mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…4). 13,25 However, the performance of CP for the OER is very low; specically the current is still lower than 10 mA cm À2 even with the overpotential of 475 mV. An overpotential as low as 360 mV was needed to reach a current density of 10 mA cm À2 , and further increasing the potential causes a steep rise of anode current, suggesting NiCo 2 O 4 nanosheet on conductive support acts as a high-performance 3D anode for oxygen evolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). 13,25 However, the performance of CP for the OER is very low; specically the current is still lower than 10 mA cm À2 even with the overpotential of 475 mV. An overpotential as low as 360 mV was needed to reach a current density of 10 mA cm À2 , and further increasing the potential causes a steep rise of anode current, suggesting NiCo 2 O 4 nanosheet on conductive support acts as a high-performance 3D anode for oxygen evolution.…”
Section: Resultsmentioning
confidence: 99%
“…For this, water electrolysis plays a fundamental role in the development of a sustainable energy system. [13][14][15][16][17] For example, cobalt-nickel oxides particles electrodeposited on glass carbon electrode displayed a high activity and stability for the OER with an overpotential of 450 mV to reach 20 mA cm À2 ; 13 McCrory et al benchmarked different OER catalysts and found that the overpotential of 380 mV at 10 mA cm À2 for CoNiO x was statistically less than that of single metal oxide; 14 Alexander Eychmüller et al developed a class of nickel cobalt oxide hollow nanosponges and found that compared with NiO and Co 3 O 4 , nickel cobalt oxide hollow nanosponges exhibit the highest catalytic activity towards the OER with the overpotential of 362 mV at 10 mA cm À2 . 9 Thus considerable research effort has been devoted to the development of anode materials with the aim of achieving highest efficiency of the OER at the lowest over potential.…”
Section: Introductionmentioning
confidence: 99%
“…Several heterogeneous and homogeneous cobalt-based OER catalysts have been recently proposed [26][27][28][29][30]. Despite these achievements, homogeneous incorporation of cobalt components into a 3D conductive framework remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many research groups have demonstrated the catalytic behavior of elemental nickel or cobalt oxides, [16,[19][20][21][22][23][24] whereas a relatively small number of studies report the electrocatalytic activity of binary nickel cobalt oxides. [9][10][11] In the present work, we demonstrate the time-dependent behavior of the OER kinetics of NiCoO x thin films in 1 m KOH (pH 14) electrolyte.…”
Section: Introductionmentioning
confidence: 99%